Correlación de los métodos California Mastitis Test (CMT), conductividad eléctrica (CE) y conteo de células somáticas (CCS) en el laboratorio de calidad de leche de la Universidad Politécnica Salesiana, Cayambe - Ecuador. 2011 - Cruz González, Eloy Guillermo, de la (2012)
As is known to the public, mastitis is a problem worldwide, and even more so when it is not detected at the early stages of the infection, this is why research has been carried out focusing on improving the methods used as tools to diagnose the subclinical mastitis, since there is no similar research with proper realities, this essay has been developed to provide local data using the available technology in the Laboratory of Milk Quality (LMQ) of the Salesian Polytechnic University, The subject is called “Correlation method California Mastitis Test (CMT), Electric Conductivity (EC) and Somatic Cell Count (SCC) in the Laboratory of Milk Quality of the Salesian Polytechnic University, Cayambe-Ecuador. 2011”, This research was possible thanks to the collaboration of the small producer Association of Pesillo (ATAC-QUEPA), where 41 samples were compiled also to the “La Alegria” and “San Carlos” dairy farms where 32 and 51 samples were taken accordingly, the samples were analyzed at the LMQ, with the purpose of correlating the suggested methods to see if it is possible to predict the SCC through CMT and EC, make a chart where the method values are related, the sensibility of methods CMT and EC regarding SCC, and observe other factors which affect the reading of the researched methods.